Modelling of carbon and nitrogen compounds removal from domestic wastewater in a modernized biological reactor - Makowska, Małgorzata; Jadanowski, Szymon; Tränckner, Jens (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
Upgrading concepts for the Bioblok MU200a wastewater treatment plant have been presented. The main goals were to achieve an effective nitrogen removal and reduce energy demand. The reference version has been presented, followed by two retrofitting options: introduction of intermittent aeration for alternating aerobic and anoxic conditions, additionally including a retrofitting option to a hybrid technology that combines advantages of activated sludge and biofilm. To design and assess both variants, the ASM3 model was used, running on the Simba# simulator. A rather complex biofilm model, necessary for the hybrid concept, was bypassed by installing a separate activated sludge proces differing in terms of sludge age and disposal of its excess sludge to the reactor. In this way, favorable technological parameters for efficient wastewater treatment could be assessed. Both upgrading concepts can be recommended for their satisfactory treatment effectiveness, feasibility in existing plants and considerable energy savings. The significance of the modelled effects was statistically confirmed by two-tailed Student’s t-test.
Environment Protection Engineering. Vol. 44, 2018, nr 4, s. 69-83
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma